2018
DOI: 10.1200/jgo.17.00090
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Pathology Turnaround Time in Botswana

Abstract: PurposeQuality pathology is critical for timely diagnosis and management of breast cancer. Few studies have analyzed pathology turnaround time (TAT) in sub-Saharan Africa. The purpose of this study was to quantify TAT for breast cancer specimens processed by the National Health Laboratory and Diagnofirm Laboratory in Gaborone, Botswana, and additionally compare TAT before and after 2012 to evaluate the effect of pathology scale-up interventions by the Ministry of Health and Wellness.MethodsRetrospective analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Although our study has not explicitly estimated the pathology result turnaround times, some portion of the diagnosis delays we observed could be attributed to prolonged pathology result turnaround times in the few available diagnostic facilities in the city. Similar to other sub-Saharan countries,47 patients with cancer in Addis Ababa waited on average for 15 days to get the pathology result 9…”
Section: Discussionmentioning
confidence: 97%
“…Although our study has not explicitly estimated the pathology result turnaround times, some portion of the diagnosis delays we observed could be attributed to prolonged pathology result turnaround times in the few available diagnostic facilities in the city. Similar to other sub-Saharan countries,47 patients with cancer in Addis Ababa waited on average for 15 days to get the pathology result 9…”
Section: Discussionmentioning
confidence: 97%
“…Possible reasons for this delay may be that the locations of tertiary care centres are widely dispersed with no clear referral infrastructure between them or that patients have financial constraints and require time to arrange for funds for the procedures or interventions. Notably, much shorter turnaround times for the initial diagnostic procedures for breast cancer management have been reported from Botswana, 15 which is one of the most developed African countries. Most patients in Ghana and Nigeria bore the full cost of their breast cancer care.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, TATs for breast biopsies in Botswana were reported at 8 days and 57 days for surgical specimens, which the authors hypothesized to be due to pre-analytical delays with a reported goal TAT of < 7 days for all specimens in the future. 18 In HICs, reported mean TATs for surgical pathology specimens and mastectomies are 2.7 and 3.8 days, respectively. 19 , 20 There is no international recommendation on TATs for histopathology reports and certainly no national consensus.…”
Section: Discussionmentioning
confidence: 99%